2023
DOI: 10.1159/000529274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Generalized Pustular Psoriasis Flares

Abstract: Background: Generalized pustular psoriasis (GPP) is a rare, neutrophilic skin disease that can become life-threatening if flares are untreated. There are limited data describing the characteristics and clinical course of GPP disease flares with current treatment options. Objective: To describe the characteristics and outcomes of GPP flares using historical medical information from patients enrolled in the Effisayil™ 1 trial. Methods: Investigators collected retrospective medical data characterizing patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…There are significant diversity in the clinical presentation and genetic background of GPP 15 . Previous studies have identified certain genotype–phenotype correlations among DITRA patients regarding disease manifestation and treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant diversity in the clinical presentation and genetic background of GPP 15 . Previous studies have identified certain genotype–phenotype correlations among DITRA patients regarding disease manifestation and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant diversity in the clinical presentation and genetic background of GPP. 15 disease manifestation and treatment response. Null IL36RN mutations were associated with GPP, while patients with hypomorphic IL36RN mutations were more likely to develop localized forms of pustular psoriasis.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…Therefore, diagnosis should not be delayed by any predefined duration of pustulation or BSA. 2,3,17 Distribution on different anatomical sites and multiple erythematous patches with pustules were considered more important clues to diagnosing GPP. There was a 100% consensus that pustular lesions on acral regions may be present during flares and should not rule out a diagnosis of GPP.…”
Section: Discussionmentioning
confidence: 99%
“…In general, pustules disappear faster than erythema when GPP is treated, including with topical, systemic, and biologic treatments. 2,3 The cytokine balance F I G U R E 1 (a) Histopathological findings for a neutrophil-filled pustule under the stratum corneum and inflammatory cell infiltrates consisting mainly of lymphocytes and neutrophils around capillaries in the papillary dermis layer (hematoxylin and eosin staining: ×100 and ×400). (b) The erythema and pustules on the lower abdomen improved after treatment.…”
Section: A Case Of Generalized Pustular Psoriasis With Discrepant Res...mentioning
confidence: 99%